UNRAVELLING THE ENIGMA OF TIME: A CRITICAL ANALYSIS OF TIME AND TEMPORALITY IN GABRIEL GARCIA MARQUEZ’S ONE HUNDRED YEARS OF SOLITUDE - Qasim Ali Kharal; Malika Batool (International Journal of Contemporary Issues in Social Sciences, 2024)
This article discuses the issue of time in One Hundred Years of Solitude (1967) novel by Gabriel Garcia Marquez with the help of Paul Ricoeur’s theory of time . This analysis examines non-linear narrative form and circularity of time to challenge conventional ideas about chronology or historiography. The investigation uses Paul Ricoeur’s theoretical framework to examine how experiences, memories, and perceptions of characters shape their understanding of time and simultaneously make distinctions between past, present and future hazy. The examination shows that this is an innovative representation of time as a complex human imposition underlying magical realism and profound questioning about human beings’ nature. In brief this exploration demystifies the secret behind ‘time’ in Gabriel Garcia Marquez’s book One Hundred Years of Solitude (1967) thereby providing insights into Marquez’s temporal landscape as well as its continuing relevance within both literary and philosophical discussions.